Characterisation of Aspergillus contaminants of milled rice and antitoxic effects of Malaysian ethnomedicinal plant extracts on growth suppression - Yazdani, Darab (2011)
Contamination of food by mycotoxins is an important food safety concern for grains and other agricultural products. Aspergillus species are responsible for production of most of these toxins including aflatoxin and ochratoxin A (OTA). Results achieved by present study revealed that 65% of the tested rice samples collected from different region in Malaysia was infected by Aspergillus and/or Eurotium species. A. flavus and A. niger were the predominant species and were the major contaminants (account for 17%) in rice. 17 Aspergillus and Eurotium isolates were obtained and identified based on morphological characteristics and molecular techniques. This study also confirmed that only A. flavus starin A2 was able to produce aflatoxins B1 and B2 in culture media. Compared with other techniques, thin layer chromatography was concluded to be a favorable method as it is simple, sensitive and reliable for detecting the aflatoxins and OTA production by Aspergillus isolates. In screening of antifungal activity of Malaysian medicinal plants, it was found that both A. galanga and P. betle significantly inhibited the production of aflatoxins by A. flavus. Compared with other extracts, the chloroform extract of A. galanga exhibited the best antifungal effect and with MIC value 25 μg/mL. P. betle extract at 500 μg/mL demonstrated a complete inhibition on the production of aflatoxins and at 100 μg/mL, the same extract was able to inhibit 69.4% of the aflatoxin production in culture media. LC-MS analysis showed that the chloroform soluble fraction of methanolic extract from A. galanga possess 10 compounds, which were mainly cinnamic acid and related aromatic acids such as coumaric acid, cafeic acid and ferulic acid, whereas in P. betle extract 11 compounds was obtained, they were mainly dihydrochalcones.